Identity in craft - Knutas, Agneta (Nordic Journal of Art & Research, 2013)
In contrast to efficiency, a bakery on the countryside in Norway is known for its slow pace of work. The slow pace allows the product, as well as the craftsperson, time in production and quality in relation to market. Therefore, the emphasis is on the importance of the aesthetic in craft, the building of identity as well as the association of tradition as part of the craft. Furthermore, allowing the time to understand both craft and tradition is what makes knowledge meaningful (Arendt, 1998/1958). Closely following craftsmen at a bakery in Norway, for two days, allowed the collection of observations and interviews. This paper is presented in narrative format. The study utilises support from Sennett (2009) and Arendt (1998/1958) in the analysis of the collected empirical data. The results regarding identity and enhancing vocational education in craft point towards the importance of concentration, judgement, an unhurried education process and a sociable master.